An Office on Main Street: Health Care Dilemmas in Small Communities - Roberts, Laura Weiss (The Hastings Center report, 1999)
The health care needs of rural populations often differ from those of their urban counterparts. And the ethical dilemmas that caregivers face are distinctively shaped in rural settings, not only by resource constraints, but by the nature of life in small, close-knit communities as well.